Perspectives on Iran's environmental policy process: Issues and constraints - Aghmashhadi, Amir Hedayati; Babu, Suresh Chandra; Daroodi, Masoud; Zahedi, Samaneh; Kazemi, Azadeh (International Food Policy Research Institute, 2018)
Due to the increase in environmental problems in Iran at the national and regional levels, it is crucial to establish sound and sustainable environmental policies. Further, it is also important to incorporate environmental considerations in the current policies being implemented in sectors such as the agriculture or energy sector. This paper applies the kaleidoscope model to understand the current policy process in Iran. Using this analysis and a literature review, we present a framework that can be applied to develop environmental policies. Studies show that the best instrument for environmental policymaking in Iran is to use the spatial planning with the double approach of activity and resource planning (based on power assessment and resource management, respectively). However, due to the environmental pressures on resources in Iran over the past decades, the current planning approach is not enough and needs to be completed in the form of resource planning.